THE ROLE OF INCREASING COMPETITIVENESS IN ENSURING ECONOMIC DEVELOPMENT (World Economics and Finance Bulletin, 2023)
The article substantiates ways to ensure economic progress by increasing the competitiveness of the national economy. Also, in the context of modern globalization, the role of foreign economic factors in increasing the competitiveness of the national economy, the role of factors is based on the possibilities of gaining a solid place in the world economy due to maintaining stable rates of economic growth through improving the investment climate in the country. Scientific proposals and practical recommendations have been formulated to ensure the improvement of the competitive environment for investment, advanced experience and the attraction of human capital due to the change in the level of openness in foreign economic policy influenced by the globalization of world economic relations, the increase in the influence of integrative groups of countries in the world economy
Keywords: World economy; competitiveness factors; production factors